Upaya Mahasiswa Membentengi Generasi Muda dari Ancaman Narkoba Konvensional dan NPS Melalui Tindakan Preventif di Perumahan Griya Hasanah Cikarang Barat - Inna Nisawati Mardiani; Astrian Hessy Defitri; Hangudi Pangasta; Kurnia Sandy; Rima Indah Sari; Ribka Marpaung (Intellektika : Jurnal Ilmiah Mahasiswa, 2024)
Due to the rising number of drug misuse cases in Indonesia, we students are involved in preventive initiatives as a means of safeguarding the next generation. In order to help raise awareness, knowledge, and prevent drug abuse among adolescents, as well as to encourage changes in adolescent behavior to be more cautious and avoid involvement in drug use, the activity with the theme "Student Efforts to Fortify the Young Generation from the Threat of Conventional Drugs and NPS Through Preventive Action in Griya Hasanah Housing, West Cikarang" was offered. A pseudo-experiment with a one-group pre- and post-test design was the study methodology used. Purposive sampling with a sample size of 22 participants is used. The pre-test, which was administered prior to the counseling session, examined the participants' level of knowledge by having them complete questions. A post-test was subsequently administered. Affective education was also used in this study to build personality, self-maturity, decision-making abilities, and the capacity to properly manage mental stress. Counseling sessions, Q&A sessions, quizzes for evaluation and feedback, and competitions were all used to carry out this activity. The study's findings demonstrated that participants' knowledge levels were low (30.8%) prior to the counseling activity and high (100%) following it. Participants had prior awareness of both conventional medications and NPS. The analysis's findings indicated a 60.2% increase in drug knowledge. The conclusion was that the younger generation's awareness and knowledge of the threat and risks of conventional drugs and NPS had increased significantly as a result of this activity.